New heterocyclic A1/A3 adenosine receptor ligands through molecular simplification strategies - Letizia Crocetti; Abigail Pearce; Venkat S. Vege; Qi Xu; Jing Xu; Hannes Buthmann; Maria Paola Giovannoni; Gabriella Guerrini; Francesca Catarzi; Silvia Selleri; Xianglin Huang; Aneesh Chandran; et al. (European Journal of Medicinal Chemistry Reports)
In this paper we report the synthesis of new A1/A3 adenosine receptor antagonists designed as simplification products of the A1 antagonists with pyrazolo[1′,5′:1,6]pyrimido [4,5-d]pyridazin-4(3H)-one scaffold previously developed by us. Notably, selective A1R antagonists are promising therapeutic agents in Alzheimer's disease and for the treatment of cognitive deficits, while A3R antagonists are potentially useful in the treatment of ischemia and certain types of cancer. Initial screening with NanoBRET competition binding assay revealed a number of products with pKi ≥5 for A1R and A3R. For some representative compounds the antagonist profiles, as well as their selectivity versus A2AR and A2BR, have been also validated by antagonizing NECA in cAMP accumulation. The most interesting compounds resulted the A1/A3 mixed antagonist 3b (pKi = 6.41 and 6.29 for A1R and A3R respectively, pKb = 5.00 and 5.27 for the A2aR and A2bR) and the selective A3R antagonist 5c (pKi = 6.40, pKb values of 4.44, 6.17, 4.16, and 4.78 for the A1R, A3R, A2aR and A2bR, respectively). Furthermore, in silico simulations were carried out to study the molecular mechanism of the high affinity of 3b for A1/A3Rs as well as the selectivity of 5c for A3R over A1R. Overall, this work highlights new series of bicyclic small-molecules as valid candidates for further structural optimization towards the development of therapeutically relevant A1/A3 adenosine receptor antagonists.